EFEKTYWNOŚĆ OPERACYJNA BANKÓW W POLSCE W LATACH 1994 - 1996 (Na przykładzie dziewięciu banków wyodrębnionych z NBP) - Kowalski, Tadeusz; Staniszewska, Danuta (Wydział Prawa i Administracji UAM, 1998)
The aim of the article is to analyse operational efficiency of nine commercial banks separated from the National Bank of Poland in 1989. The background of this analysis is a presentation and evaluation of principal institutional and economic factors that do influence the banking sector. The notion of operational efficiency of this sector can be defined as an ability of banks to operate effectively their current activities under market circumstances and competition. Operational efficiency during macro-economic transformation depends heavily on external factors particularly, institutional ones. The impact of these factors stems from the need to implement deep changes in qualitative policy changes in economic structure and in the role of public sector borrowing requirement. The latter is still very important thanks to the underdevelopment of financial intermediation and shallow money market in Poland. The work has two parties. The first part presents a discussion and an analysis of institutional and economic conditions prevailing around the banking sector in Poland during early stage transformation. Knowledge of these condition is necessary to understand and then interprete changes occurring in operational efficiency of banks. Most new legal regulations in banking sector have been introduced between 1989 and 1994. The Authors have assumed that quantitative analysis of operational efficiency in 1989 -1993 would be neovily biased by frequent, major changes of banks’ institutional environment. This analysis has been done for relatively homogenous group of nine banks created in 1989 on the basis of regional branches of the National Bank of Poland. Second part of the paper was devoted to presentation of the results of quantitative analysis of operational efficiency in the group of the nine banks. Examination of effectiveness was done using generalized DuPont method and a matrix approach.
OPERATIONAL EFFICIENCY OF POLISH BANKS IN 1994 - 1996 (The case of nine commercial banks separated from the National Bank of Poland in 1989)